The proficiency of communication in mother tongue among Kadazandusun students from local universities in Sabah / Jeinorvay Vitalis Tongkul and Kevin George Duat - Tongkul, Jeinorvay Vitalis; Duat, Kevin George (2015)
Malaysia is a multiracial and multicultural country. David (2006) stated that one of the issues that often arise in a country like Malaysia where over a hundred languages and dialects are spoken daily by the people is the choice of language. Malaysia, made up of Peninsular Malaysia (West Malaysia) and Sabah and Sarawak (East Malaysia), is a nation of diverse ethnicity. According to Malaysia Demographics Profile (2014), it was estimated that there are about 30,073,353 populations in July 2014. The populations comprises of multiracial and different ethnicity which divided into Malay (50.1%), Chinese (22.6%), indigenous (11.8%), Indian (6.7%), other (0.7%), non-citizens (8.2%). Among the thirteen states in Malaysia, Sabah is often referred as the Land Below The Wind. Among the 2626.3 ("000) population in Sabah, there are 32 officially recognized ethnic groups and they are referred as the indigenous people or the bumiputra or the non-bumiputra (Department of Statistics, Malaysia). There are Kadazan-Dusun: 17.8%, Rungus, Bajau: 13.4%, Malay: 11.5%, Murut: 3.3%, Other bumiputra: 14.6%, Chinese (majority Hakka): 13.2%, Other non-bumiputra: 4.8%, and the Non-Malaysian citizen: 5%. Different ethnic can be seen through different regions in Sabah such as the North, South, West and East region. According to Summer Institute of Linguistic, language is intimately tied to society and culture. The native language or the mother tongue represents the ethnic itself and preserving the language is likely to be the obligation from generation to generation. The practice of the language usually shows when they used the language in their daily conversation with families, neighbors, among villagers and everywhere despite looking at the age of the person. The Parliament Speaker Tan Sri Pandikar Amin Mulia that come from the indigenous background got the attention from Education Ministry for having a teaching subject that teaches the heritage language and now the policy can be seen in pre-schools and also the higher institution such as University Malaysia Sabah. The Information and Broadcasting Minister Senator Pervaiz Rashid South Asian Broadcasting Agency (SABAH) emphasized that the mother tongue aims to deepen and enrich knowledge of the people. Mother languages play important role in development of literature and it is the most powerful instrument of preserving and developing national heritage.